2011
DOI: 10.1007/s12032-011-9885-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-like receptor 4 and beta 1 integrin in breast cancer

Abstract: Toll-like receptor (TLR) 4 signaling pathway has been shown to support tumor cell growth in vitro and in vivo. Its stimulation on breast cancer cell lines induces β1 integrin and promotes tumor invasiveness. However, its role in predicting clinical behavior of tumor is not yet clarified. Therefore, we investigated TLR4 and β1 integrin expression on 133 primary breast cancer samples by immunohistochemistry and correlated it with overall survival and disease-free survival of patients as well as with clinicopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…In conclusion, our results suggest that the SPA4 peptide has potential to be further developed as an immunotherapeutic strategy to limit inflammation-induced cancer. It is expected that SPA4 peptide may be of clinical utility in other types of cancer where the activation of TLR4 has been shown to exert oncogenic effects 32 , 33 , 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our results suggest that the SPA4 peptide has potential to be further developed as an immunotherapeutic strategy to limit inflammation-induced cancer. It is expected that SPA4 peptide may be of clinical utility in other types of cancer where the activation of TLR4 has been shown to exert oncogenic effects 32 , 33 , 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…For statistical analysis we used the same method established by Petricevic and colleagues [21] where the results were presented as a positive (strong positive staining 3+ and moderately positive staining 2+) or a negative (weak positive 1+ and negative staining 0) for tumor cells.…”
Section: Methodsmentioning
confidence: 99%
“…This is highly pertinent given that protein function and protein localisation are closely correlated. Studies have also shown that accounting for protein localisation can be an essential requirement to identifying correlations with other proteins when applying the IHC technique [48]. To date, very few studies have evaluated the prognostic significance of differential protein distribution within diagnostic breast cancer tissue samples.…”
Section: Discussionmentioning
confidence: 99%